FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DENGAN REPUTASI KAP SEBAGAI VARIABEL PEMODERASI (STUDI PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2015 - 2019) - Fuad Rahardi; Afrizal Afrizal; Enggar Diah P. Arum (Magister Ilmu Akuntansi Universitas Jambi, 2021)
This study aimed to analyze the effect of company size, audit opinion, solvency, profitability and audit committee on audit delay with the reputation of Public Accountant as a moderating variable. The population of this study were companies listed in the LQ-45 index in the Indonesia Stock Exchange on 2015 - 2019. The sampling technique used was purposive sampling method, that the samples were selected based on the suitability of the sample characteristics with the specified samples selection criteria. Data analysis in this study used panel data analysis and absolute difference test. The results of this study indicated that: solvency and audit committee had a positive and significant effect on audit delay, while profitability had a negative and significant effect on audit delay. Meanwhile, company size and audit opinion had no effect on audit delay. The results of this study also showed that the reputation of KAP was able to moderate the relationship between firm size and solvency with audit delay and was unable to moderate the relationship between audit opinion, profitability and audit committee with audit delay.